The Influence of Digital Leadership Implementation, Agile Working, and Collaboration Technology on the Performance of Employees at PT. Sanly Industries - Rasika Rasika; Raniasari Bimanti Esthi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the influence of digital leadership, agile working, and collaborative technology on employee performance at PT. Sanly Industries. The research is motivated by the growing importance of digital transformation in modern business environments, where leadership styles, work flexibility, and technological collaboration significantly affect organizational success. In today's dynamic and fast-paced digital era, companies are increasingly required to adapt quickly and innovate continuously. Digital leadership refers to a leader’s ability to drive digital transformation by leveraging digital tools, fostering innovation, and encouraging open communication. Agile working, which emphasizes flexibility, autonomy, and adaptability in work arrangements, is also critical in ensuring responsiveness to change. Moreover, collaborative technology—such as digital platforms and communication tools—facilitates real-time interaction and teamwork, ultimately improving employee efficiency and coordination. This research adopts a quantitative method with a descriptive associative approach. Data was gathered through the distribution of structured questionnaires to employees at PT. Sanly Industries. The collected data were then analyzed using multiple linear regression to determine the relationship between the independent variables (digital leadership, agile working, and collaborative technology) and the dependent variable (employee performance). The results of the study reveal that each of the three independent variables—digital leadership, agile working, and collaborative technology—has a positive and statistically significant effect on employee performance. Furthermore, when analyzed simultaneously, these variables collectively demonstrate a strong influence, as indicated by a high coefficient of determination. This suggests that improvements in these areas contribute meaningfully to enhanced employee performance. The findings underscore the need for organizations to invest in digital leadership development, promote agile work cultures, and implement effective collaborative technologies as part of an integrated strategy to boost employee productivity and organizational performance in the digital era.